ART in HIV-Positive Persons With Low Pretreatment Viremia: Results From the START Trial. (1st August 2019) - Sereti, Irini; Gulick, Roy M.; Krishnan, Sonya; Migueles, Stephen A.; Palfreeman, Adrian; Touzeau-Römer, Veronique; Belloso, Waldo H.; Emery, Sean; Law, Matthew G.
Abstract : Background: The benefit of immediate antiretroviral therapy (ART) at CD4 >500 cells/μL was established in the Strategic Timing of Antiretroviral Treatment (START) study. The benefits and risks of immediate ART in participants with low pretreatment viremia, including virologic suppressors, were further assessed. Setting: Randomized prospective international study. Methods: START participants with enrollment viremia <3000 c/mL were included. We compared clinical outcomes (grade 4 adverse events, hospitalizations, or death), plasma viremia, CD4 counts, and changes in biomarkers in immediate versus deferred ART groups. Results: Participants (N = 1134 including 93 with viremia ⩽50 c/mL) had a median age of 37 years, 40% were women, and median CD4 was 713 cells/µL. Ninety-seven percent in the immediate and 29% in the deferred arm initiated ART at a median of 6 and 699 days, respectively. Clinical outcomes were experienced in 64 versus 61 patients in immediate and deferred arms (hazard ratio 1.10, 95% confidence interval: 0.77 to 1.56). The CD4 count difference was 125 cells/µL at 12 and 235 cells/µL at 36 months higher in the immediate versus deferred groups. D-dimer and VCAM levels decreased, and C-reactive protein increased, in the immediate arm at month 8. No significant changes in CD4 counts or biomarkers were observed in persons who maintained spontaneous virologic suppression. Conclusions: START participants with low enrollment viremia experienced higher CD4 counts, greater proportion with suppressed viremia, and decreases in D-dimer levels on immediate ART despite the lack of difference in serious clinical outcomes. These data support immediate ART in people with low viremia, although equipoise remains for suppressors. Abstract : Supplemental Digital Content is Available in the Text.